A Tm-Bi Co-Doped Fiber Laser with Dual Pumping Operation - Saidin, N.; Harun, Sulaiman Wadi; Damanhuri, S.S.A.; Ali, S.M.M.; Ahmad, Harith; Halder, A.; Paul, Mukul Chandra; Das, S.; Pal, M.; Bhadra, S.K. (Institute of Physics, 2013)
We demonstrate an efficient fiber laser operating at 1901.6 nm using a newly developed thulium bismuth co-doped fiber (TBF) with dual pumping at 792 nm and 1552 nm. The fiber was fabricated using modified chemical vapor deposition and solution doping processes. The dopant concentrations (wt%) and compositions inside the core are 0.15 Bi2O3, 0.3 Tm2O3, 1.0 Al2O3 and 12.0 GeO2. The TBF laser operates at 1901.6 nm with a lasing efficiency of 33.2% and pump power threshold of 85 mW using a 2-m-long TBF in a linear cavity with two fiber Bragg gratings (FBGs). The high efficiency is attributed to the use of additional 1552 nm pump to complement 792 nm pumping. The maximum output power of 225 mW is achieved at the pump power of 820 mW with the optimum length of 2 m.